Intronic CRISPR repair in a preclinical model of Noonan Syndrome-Associated Cardiomyopathy - Hanses, Ulrich; Kleinsorge, Mandy; Roos, Lennart; Yigit, Gökhan; Li, Yun; Barbarics, Boris; El-Battrawy, Ibrahim; Lan, Huan; Tiburcy, Malte; Hindmarsh, Robin; Lenz, Christof; Salinas, Gabriela; et al. (Circulation, 2020)
Background: - Noonan syndrome (NS) is a multisystemic developmental disorder characterized by common, clinically variable symptoms, such as typical facial dysmorphisms, short stature, developmental delay, intellectual disability as well as cardiac hypertrophy. The underlying mechanism is a gain-of-function of the RAS-mitogen-activated protein kinase signaling pathway. However, our understanding of the pathophysiological alterations and mechanisms, especially of the associated cardiomyopathy, remains limited and effective therapeutic options are lacking. - Methods: - Here, we present a family with two siblings displaying an autosomal recessive form of NS with massive hypertrophic cardiomyopathy as clinically the most prevalent symptom caused by biallelic mutations within the leucine zipper-like transcription regulator 1 (LZTR1). We generated induced pluripotent stem cell-derived cardiomyocytes of the affected siblings and investigated the patient-specific cardiomyocytes on the molecular and functional level. - Results: - Patients’ induced pluripotent stem cell-derived cardiomyocytes recapitulated the hypertrophic phenotype and uncovered a so-far-not-described causal link between LZTR1 dysfunction, RAS-mitogen-activated protein kinase signaling hyperactivity, hypertrophic gene response and cellular hypertrophy. Calcium channel blockade and MEK inhibition could prevent some of the disease characteristics, providing a molecular underpinning for the clinical use of these drugs in patients with NS, but might not be a sustainable therapeutic option. In a proof-of-concept approach, we explored a clinically translatable intronic CRISPR (clustered regularly interspaced short palindromic repeats) repair and demonstrated a rescue of the hypertrophic phenotype. - Conclusions: - Our study revealed the human cardiac pathogenesis in patient-specific induced pluripotent stem cell-derived cardiomyocytes from NS patients carrying biallelic variants in LZTR1 and identified a unique disease-specific proteome signature. In addition, we identified the intronic CRISPR repair as a personalized and in our view clinically translatable therapeutic strategy to treat NS-associated hypertrophic cardiomyopathy.